Risk Factor Analysis of Calcification in Aortic and Mitral Valves in Maintenance Peritoneal Dialysis Patients - Chunyuan Wang; Linsen Jiang; Sheng Feng; Yongbing Shi; Huaying Shen; Xiaosong Shi; Zhi Wang; Yin Zeng (Karger Publishers, 2013)
Background/Aims: This study aimed to investigate potential risk factors for calcification in aortic and mitral valves in maintenance peritoneal dialysis (MPD) patients. Methods: We enrolled MPD patients who had undergone over 18 months of dialysis in our dialysis center, examined their cardiac valve calcification status by echocardiography, and recorded their biochemical data and dialysis-related indicators. These results were compared by logistic regression analyses to identify the risk factors associated with calcification in aortic and mitral valves. Results: Among the 117 enrolled MPD patients, 41 exhibited calcification in aortic or mitral valves, including 38 with aortic valve calcification (AVC) and 17 with mitral valve calcification (MVC); 14 of them had calcification in both aortic and mitral valves. Multivariate logistic regression analysis revealed that age (OR=1.965, p=0.01), diabetes history (OR=4.693, p=0.029), calcium-phosphorus product (OR=2.373, p=0.001) and prealbumin (OR=0.908, p=0.012) were independently related to AVC, whereas age (OR=3.179, p=0.023), calcium-phosphorus product (OR=6.512, p=0.001), prealbumin (OR=0.885, p=0.033), high-density lipoprotein (OR=19.540, p=0.011) and diabetes history (OR=6.948, p=0.038) were independently related to MVC. Conclusions The incidence of cardiac valve calcification in MPD patients is high, and the incidence of AVC is higher than MVC. Age, diabetes history, calcium-phosphorus product and hypo-prealbuminemia are independent risk factors for AVC, whereas age, calcium-phosphorus product and hypo-prealbuminemia are independent risk factors for MVC.